Tuning infrared plasmon resonances in doped metal-oxide nanocrystals through cation-exchange reactions - Zeke Liu (Nature Portfolio, 2019)
Doping semiconductor nanocrystals with impurity atoms is a key pathway for tuning their plasmonic properties. Here, the authors use a cation exchange strategy to dope p-type or n-type metal ions into n-type metal-oxide nanocrystals, post-synthetically tailoring their localized surface plasmon resonances in the infrared region.